Pengaruh Ratio Profitabilitas dan Ratio Aktivitas Terhadap Current Ratio pada Perusahaan Sub Sektor Pulp dan Kertas yang Terdaftar di Bursa Efek Indonesia - Hade Chandra Batubara; Astri Annisa Putri (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this research is to see the effect of profitability ratios and activity ratios on current ratios in pulp and paper sub-sector companies listed on the Indonesia stock exchange for the 2013-2017 period. The variables used in this research are Current Ratio, Return On Asset, Return On Equity, Total Asset Turnover and Working Capital Turnover. The approach used in this research is an associative approach. The data technique in this study is to use the documentation method, namely financial statements in the form of balance sheets and income statements in the Pulp and Paper Sub-Sector companies listed on the Indonesia Stock Exchange. The data analysis technique used in this research is multiple linear regression, the simultaneous classical assumption test, and the coefficient of determination. Data processing in this study used the SPSS (Statistic Package for the Social Sciens) 20.00 software program for Windows. The results of this study indicate that partially Return On Asset has a significant positive effect on Current Ratio, Return On Equity has a significant positive effect on Current Ratio, Total Asset Turnover has a significant positive effect on Curren Ratio, Working Capital Turnover has a significant positive effect on Curren Ratio. Simultaneously, Return On Asset, Return On Equity, Total Asset Turnover and Working Capital Turnover have a significant positive effect on the Current Ratio.